رمزية المكان في فنون الحداثة وأثرها على التذوق الفني - العتباني، أشرف أحمد; محمد، أميمة سعيد أحمد; عبدالبديع، هاني علي (جامعة عين شمس - كلية التربية النوعية, 2019)
The study dealt with the concept of symbolic significance in the art of modernity and the influence of the place element and its role in achieving the process of good artistic taste and clarifying the value of the symbol, where recognition of the place is an effective way to realize the aesthetics of the symbol and the dissemination of artistic values and influence on the ideology of the recipient of these works It is a change in the comprehensive view of the arts of modernity (as a new vision) of these works. And through the knowledge of the researcher and his readings in the field of specialization noted the richness of the arts of modernity in many dimensions of plastic, aesthetic and philosophical that develop the artistic perception and raise the general taste of the recipients of this art, In addition to the use of the researcher to analyze the element of place in some elements of the arts of modernity, which had the largest role in taking advantage of the element of place as a symbolic symbol in the arts of modernity. So that I was able to answer the problem of research, namely: that the place affects the visual perception of the arts of modernity and how it is in the work of art linked to the framework of civilization time: - The place in Impressionism school is a physical concept. - How far does the character of “Osman Abdel Basit” go in harmony with “Ameen Sedky” and “Badeih Khairy”? - To what extent the writer is shaping the model of the “Barbarian” to that copes with the actor’s ability and nature of his personality? - To what extent the comedian can control the exposed thoughts inside the text? Results: - Both “Ameen Sedky” and “Badeih Khairy” count on some strategies in transform the narration (tale) inside the text structure; some of these strategies are: wrong deduction, role exchange, hiding and disguising tricks, in addition to exaggeration of matters and non¬logicality of situation and dialogue. - Both “Ameen Sedky” and “Badeih Khairy” count on language besides the dramatic structure as a means for humor, so, they both have employed cursing, insulting and verbal swindle besides different accents that count on jokes, quips and rhyme. As for Badeih- this reciter of zajal poem, the researcher has found out that he has been creative more than Sedky in employing language as a mechanism for humor and laughing in his theatre. - The study also proves that the Egyptian theatre - in that period-has not exposed or discussed essential issues touching likely the Egyptian society and this because it has focused mainly on comedy. The study also reflects consistency and harmony exists in the character of Osman Abdel Basit as presented by both Ameen Sedky” and “Badeih Khairy.
Keywords: الدلالة -- الرمز -- فنون الحداثة -- التذوق الفنى